2021
DOI: 10.1111/ntwe.12202
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the ‘Future of Work’: An analysis of the policy discourse

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Developments in technology may actually increase the number of jobs available, due to rising demand and 'spill over effects' (Gregory et al, 2016), and will also alter existing jobs, increasing the level of skill required as technology undertakes the more routine aspects of some roles (Özkiziltan & Hassel, 2020). Business consulting groups with particular interests are argued to have heavily influenced the policy discourse on the 'Future of Work' and automation, presenting the solution to the 'Machine v. Human' challenge as the 'upskilling' of the latter to accommodate the former (Schlogl et al, 2021). 2 Acemoglu and Restrepo's (2019) framework encapsulates these debates, highlighting three effects of automation.…”
Section: Automation Work and 'Good Jobs'mentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in technology may actually increase the number of jobs available, due to rising demand and 'spill over effects' (Gregory et al, 2016), and will also alter existing jobs, increasing the level of skill required as technology undertakes the more routine aspects of some roles (Özkiziltan & Hassel, 2020). Business consulting groups with particular interests are argued to have heavily influenced the policy discourse on the 'Future of Work' and automation, presenting the solution to the 'Machine v. Human' challenge as the 'upskilling' of the latter to accommodate the former (Schlogl et al, 2021). 2 Acemoglu and Restrepo's (2019) framework encapsulates these debates, highlighting three effects of automation.…”
Section: Automation Work and 'Good Jobs'mentioning
confidence: 99%
“…Certainly the edict ‘thou shalt upskill!’ (Schlogl et al, 2021, p. 14) is applicable to the care workers, with a policy focus on the skills deficit of a workforce purportedly being left behind by fast‐moving technological developments (DHSC, 2021; NHS & PHE, 2017). …”
mentioning
confidence: 99%
“…On a more general level, a review of policy-focused literature identified a dominant narrative that treats current digital innovations primarily as a prime cause of challenges for the labour market, while the primary responsibility for being able to operate successfully in this market is put on individuals in the form of 'upskilling' [57]. This impression is partially contradicted by another study, which shows only small effects of technological change on changing skills use, while the changing working environment seems to have larger effects [58].…”
Section: Required Qualificationsmentioning
confidence: 99%
“…Next to | 345 that, lately, workers are held responsible for aligning their skillset with the expected skill requirements due to technological change. In a study of the future-of-work literature, Schlogl et al (2021) conclude that technology is seen as a prime cause of challenges in the labour market and requires individuals to start upskilling. Even though some scholars addressed the importance of the working environment-people's interaction with machines, and each other is highly dependent on the local context- (Bal et al, 2021;Cascio & Montealegre, 2016;Hodder, 2020), this aspect gained not so much attention.…”
Section: Technological Change and Skills Usementioning
confidence: 99%
“…Consequently, the expectations about the future of work and skills use are underpinned with a lot of survey material, focusing on skills' economic and psychological features. Schlogl et al (2021) discuss this policy‐focused and grey literature and see a dominant narrative focused on placing the responsibility to deal with the future of work in the form of ‘upskilling’. The analysis of the survey material itself used in this narrative needs to be considered too.…”
Section: Introductionmentioning
confidence: 99%